2021
DOI: 10.1002/cpdd.1020
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Repository Corticotropin Injection Compared With Synthetic ACTH1‐24 Depot and Methylprednisolone in Healthy Subjects

Abstract: Repository corticotropin injection (RCI; Acthar Gel) is a naturally sourced complex mixture of adrenocorticotropic hormone (ACTH) analogs and other pituitary peptides. This phase 1, single-center, open-label, randomized parallel study directly compared the pharmacokinetics and pharmacodynamics of RCI and synthetic ACTH 1-24 depot. Methylprednisolone was included to estimate the steroidogenic exposure of RCI and synthetic ACTH 1-24 depot when used to treat nephrotic syndrome. A total of 48 healthy subjects aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…These side effects are consistent with those seen with glucocorticoids [61]; this may be expected considering that endogenous production of cortisol from the adrenal cortex is one of the mechanisms of RCI, albeit at lower levels than observed with other MCR agonists [31]. However, RCI is multi-mechanistic in that it may also cause direct modulation of immune cells, such as B cells and macrophages, independently of steroids [28,31]. This is supported by a recent systematic review showing distinct AE profiles between RCI and glucocorticoids in the treatment of rheumatoid arthritis [64].…”
Section: Therapeutic Options For Pulmonary Sarcoidosissupporting
confidence: 84%
See 2 more Smart Citations
“…These side effects are consistent with those seen with glucocorticoids [61]; this may be expected considering that endogenous production of cortisol from the adrenal cortex is one of the mechanisms of RCI, albeit at lower levels than observed with other MCR agonists [31]. However, RCI is multi-mechanistic in that it may also cause direct modulation of immune cells, such as B cells and macrophages, independently of steroids [28,31]. This is supported by a recent systematic review showing distinct AE profiles between RCI and glucocorticoids in the treatment of rheumatoid arthritis [64].…”
Section: Therapeutic Options For Pulmonary Sarcoidosissupporting
confidence: 84%
“…Possible side effects of RCI may include change in glucose tolerance, hypertension, and increased appetite and weight gain [ 60 , 61 , 63 ]. These side effects are consistent with those seen with glucocorticoids [ 61 ]; this may be expected considering that endogenous production of cortisol from the adrenal cortex is one of the mechanisms of RCI, albeit at lower levels than observed with other MCR agonists [ 31 ]. However, RCI is multi-mechanistic in that it may also cause direct modulation of immune cells, such as B cells and macrophages, independently of steroids [ 28 , 31 ].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The anti-inflammatory mechanism of action for RCI was originally thought to be via activation of MC2R on adrenocortical cells, which stimulates production of endogenous cortisol; however, recent evidence has shown that RCI has relatively low agonistic activity of MC2R [ 20 , 21 ]. This is supported by studies in animals [ 20 ] and healthy human subjects [ 21 , 22 ], which showed lower levels of endogenous corticosteroid production after administration of RCI compared to synthetic ACTH 1–24 (Fig. 1 ).…”
Section: Rci For the Treatment Of Slesupporting
confidence: 58%
“…ACTH 1–24 first 24 amino acids of adrenocorticotropic hormone, RCI repository corticotropin injection, SEM standard error of the mean. Reproduced from Poola et al [ 22 ] under the CC BY-NC-ND 4.0 open access license …”
Section: Rci For the Treatment Of Slementioning
confidence: 99%